A De Novo PTEN Pathogenic Variant in a Young Girl with Sporadic Cowden Syndrome—A Case Report - Paulina Gebhart; Christian Singer; Daniela Muhr; Christina Stein; Yen Y. Tan (Pediatric Reports, 2025)
Cowden syndrome (CS) is a rare hereditary disorder characterized by benign overgrowth in various tissues and a high risk of breast and thyroid cancer. CS is closely associated with pathogenic variants (PVs) in the phosphatase and tensin homolog (PTEN) tumor suppressor gene. PVs in PTEN are usually inherited and estimates of de novo frequencies remain inconclusive. The diagnosis of PTEN-associated syndromes remains a challenge in clinical practice, due to patients showing seemingly unrelated symptoms. We report on the clinical management of a now 18-year-old female CS patient, who initially presented with macrosomia, motor development delay and later, lipomas on the abdominal wall. Genetic testing revealed a de novo PTEN PV c.1003C>T(p.Arg335X). The PV was detected in leukocyte DNA of the patient. Using direct DNA sequencing, as well as NGS, the PV was not found in any of the tissues derived from immediate family members. However, the PV was detected in multiple samples representing other germ layers of the affected patient, which renders constitutional mosaicism unlikely. This case constitutes the first description of a de novo PTEN PV, in which constitutional mosaicism was systematically ruled out and underscores the importance of timely genetic testing of patients and their relatives. The diagnosis of a PTEN PV in early childhood allows for the implementation of a comprehensive, lifelong care plan that addresses both pediatric and adult medical needs as well as cancer risk surveillance and family planning. This not only accounts for the affected patients, but also their close family members who might be susceptible to the same PV.